Kontestasi dan Reintegrasi Nilai-nilai Islam pada Tradisi Tabot: Studi Hubungan Perayaan Tabot dengan Kesadaran Mitigasi Bencana di Bengkulu - Hurin’in AM; Liza Wahyuninto; Erlina Zanita (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
This article aims to analyze the contestation and reintegration of Islamic values ​​in the Tabot tradition of the West Coast coastal community of Sumatra, especially Bengkulu Province, on awareness of disaster mitigation. The method used is through direct interviews conducted in depth to selected informants which include religious leaders, traditional leaders, community leaders and disaster experts. The results show that there is a contestation of implementation and meaning in the Tabot tradition. Tabot which was the beginning of religious activities became a cultural activity to become a joint activity and even something that the Bengkulu people had been waiting for. The Tabot tradition forms trust and is interpreted as a goal for the ancestors, by rejecting balak (disaster), various things in life and bringing peace. This local knowledge is passed down from generation to generation and is used as a local-based disaster mitigation.